Slip rate deficit and earthquake potential on shallow megathrusts - Lindsey, Eric Ostrom (2022)
Most destructive tsunamis are caused by seismic slip on the shallow part of offshore megathrusts. The likelihood of this behaviour is partly determined by the interseismic slip rate deficit, which is often assumed to be low based on frictional studies of shallow fault material. Here we present a new method for inferring the slip rate deficit from geodetic data that accounts for the stress shadow cast by frictionally locked patches, and show that this approach greatly improves our offshore resolution. We apply this technique to the Cascadia and Japan Trench megathrusts and find that wherever locked patches are present, the shallow fault generally has a slip rate deficit between 80 and 100% of the plate convergence rate, irrespective of its frictional properties. This finding rules out areas of low kinematic coupling at the trench considered by previous studies. If these areas of the shallow fault can slip seismically, global tsunami hazard could be higher than currently recognized. Our method identifies critical locations where seafloor observations could yield information about frictional properties of these faults in order to better understand their slip behaviour.